Pemanfaatan Aromaterapi Lemon untuk Mengurangi Kecemasan pada Ibu Hamil : Pendekatan Non-Farmakologis dalam Meningkatkan Kesehatan Mental - Novi Rida Eriyani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Anxiety experienced by pregnant women is a common psychological problem and can have a significant negative impact on maternal health and fetal development. This anxiety can be caused by various factors, including physical changes, concerns about the delivery process, and new responsibilities as parents. Therefore, it is important to find effective ways to address this anxiety. One non-pharmacological approach that can be implemented is the use of lemon aromatherapy, which is known to have calming and relaxing properties. This activity aims to increase the knowledge and skills of pregnant women in utilizing lemon aromatherapy as a method to reduce their anxiety. This activity was held in June 2025 at PMB Lismarini, involving 20 pregnant women who actively participated in this program. The method used in this activity included several stages: education on the benefits of aromatherapy, demonstrations on how to use it, hands-on practice using lemon aromatherapy, and evaluation conducted through pre- and post-tests to measure changes in participants' anxiety levels. The results of this activity showed a significant decrease in participants' anxiety levels. Previously, many pregnant women were in the severe and moderate anxiety categories, but after participating in the activity, they shifted to mild anxiety and even no anxiety. Lemon aromatherapy has been proven effective in providing relaxation and reducing emotional tension experienced by pregnant women. Therefore, this activity is expected to become a promotional educational model in maternal health services. Through this approach, it is hoped that pregnant women will better understand and utilize aromatherapy as a way to maintain their mental health during pregnancy. Furthermore, this activity can also provide health workers with insight into the importance of non-pharmacological approaches in supporting the mental health of pregnant women.